Nutritional Status Predicts Hospital Length of Stay in Meningioma Patients. (16th November 2020) - Huq, Sakibul; Khalafallah, Adham M; Jimenez, Adrian; Kedda, Jayanidhi; Bachu, Vismaya; Lam, Shravika; Camp, Samantha; Horowitz, Melanie; Azmeh, Omar; Mukherjee, Debraj
Abstract: INTRODUCTION: Hospital length of stay (LOS) is a substantial driver of costs within neurosurgery and an attractive outcome for quality improvement initiatives in the era of value-based payment models. Nutritional status (NS) is a clinically modifiable characteristic known to predict LOS in surgical patients. However, NS has not been studied in patients with meningioma, the most common primary brain tumor. METHODS: We retrospectively reviewed data for meningioma patients who underwent surgery from 2017–2019 at our institution. Prolonged LOS was defined as greater than median. The optimal cutpoint delineating high/low albumin was identified using maximally selected rank statistics. Patient characteristics were compared between high/low albumin groups using Fisher's exact and Mann Whitney tests. The predictive value of albumin upon LOS, and high/low albumin upon prolonged LOS, were identified using stepwise multivariable linear and logistic regression, respectively. RESULTS: Out of 358 patients, preoperative albumin was available for 190, which were subsequently included in our analysis. Our analysis cohort had a mean age of 58.7 and 5-factor modified frailty index (mFI-5) of 0.88. The majority of patients were female (75%) and Caucasian (66%) with a WHO Grade 1 tumor (87%) that received Simpson grade 1 (40%) resection. Median LOS was 3 days. Median albumin was 4.4g/dL with an optimal cutpoint of >3.7g/dL. Patients with low albumin tended to be more frail ( P = .0020) and have higher-grade tumors ( P = .041). After adjusting for age, mFI-5, WHO grade, and Simpson grade, each 1 g/dL increase in albumin was associated with a 2.48-day decrease in LOS ( P = .030). Similarly, low albumin (≤3.7g/dL) was associated with increased odds of prolonged LOS (adjusted odds ratio 4.51, P = .008). CONCLUSION: Nutritional status is a modifiable factor that is strongly associated with LOS in meningioma patients. While external validation is needed, our data suggest that nutritional intervention should be considered for patients with a preoperative albumin at or below 3.7g/dL in order to reduce the risk of prolonged LOS.